Disability and the future of work - Hyseni, Fitore; Schur, Lisa; Kruse, Douglas; Blanck, Peter (Research in social science and disability ;, 2025)
The employment landscape is evolving rapidly, driven by technological innovations, shifting employer practices, and new government policies that redefine where and how work is performed. However, these transformations have not been universally beneficial. Future research is required to explore the potential disproportionate impact they might have on marginalized populations already excluded from the labor market. People with disabilities are one group who continue to have a low employment rate in the United States (U.S). They are also more likely than those without disabilities to work part-time or in precarious jobs with less job security, lower pay and benefits, and minimal worker protections. This volume of Research in Social Science and Disability brings together leading research that examines how systemic policies and practices, pandemic-driven transformations, and strategies for diversity, equity, and inclusion (DEI) continue to shape the employment landscape for workers with disabilities. Disability and the Future of Work explores changing workplace dynamics and proposes strategies for fostering an inclusive and equitable future of work for people with disabilities.